Precipitation of Occult Lymphomatous Hemorrhage by Early Initiation of Factor Xa Inhibitors: A Pharmacovigilance Case Study and Critical Reappraisal of DOAC Safety - Kadek Cahya Adwitya; I Putu Bayu Triguna (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: The concurrent management of cancer-associated thrombosis (CAT) and active malignancy represents a precarious clinical equilibrium, particularly when the neoplasm involves occult extranodal gastrointestinal (GI) sites. While direct oral anticoagulants (DOACs) have largely supplanted low-molecular-weight heparin (LMWH) as the standard of care for CAT, emerging pharmacovigilance data suggest a specific vulnerability in patients with luminal GI malignancies. Case presentation: We report the case of a 76-year-old frail female presenting with extensive left iliofemoral deep vein thrombosis (DVT). Diagnostic evaluation identified a perfect storm of pathology: Stage IV diffuse large B-cell lymphoma (DLBCL) with bulky retroperitoneal lymphadenopathy encasing the inferior vena cava (IVC) and a suspicious infiltrative mass in the proximal jejunum. Following standard guidelines, the patient was initiated on rivaroxaban. However, this intervention precipitated a catastrophic upper GI hemorrhage (hemoglobin drop to 6.5 g/dL) within 96 hours. A retrospective pharmacokinetic audit revealed critical predisposing factors: severe hypoalbuminemia (1.6 g/dL) increasing the free drug fraction, and an estimated glomerular filtration rate (eGFR) <30 mL/min, suggesting the patient was effectively overdosed relative to her physiological clearance. Conclusion: The empiric use of rivaroxaban in elderly patients with uncharacterized abdominal masses, renal impairment, and cachexia carries unacceptable hemorrhagic risks. We advocate for a systematic bleed-risk stratification protocol, prioritizing LMWH or Apixaban, and the judicious use of IVC filters as bridging therapies in high-risk phenotypes.